THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF A TECHNOLOGY FOR DEVELOPING INFORMATION-ANALYTICAL COMPETENCE IN FUTURE TEACHERS: STRUCTURE AND DEVELOPMENT MECHANISMS - Bakhtiyorjon Madaliyev (Bright Mind Publishing, 2026)
This article analyzes the structural components of information-analytical competence and the theoretical mechanisms that support its development in contemporary teacher education. Information-analytical competence is defined as an integrated set of cognitive, evaluative, and reasoning processes that enable future teachers to manage complex information flows, critically interpret content, and produce evidence-based conclusions. The study argues that this competence comprises interconnected domains including information retrieval, source credibility assessment, analytical interpretation, and argument-based reasoning. It also outlines key pedagogical conditions for developing these domains, emphasizing digital information culture, metacognitive awareness, systematic reasoning, and targeted work on bias recognition and evidence synthesis. The article synthesizes national pedagogical perspectives with international theoretical approaches to justify information-analytical competence as a core requirement for teachers working in information-saturated educational contexts.
Keywords: Information-analytical competence, cognitive processes, analytical interpretation, information evaluation, reasoning mechanisms, critical processing, digital information culture, metacognition, teacher education, information literacy, critical thinking, source credibility, cognitive bias, analytical skills, pedagogical strategies.